2007
DOI: 10.1103/physrevb.75.094423
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance and efficiency measurements ofAlq3-based OLEDs

Abstract: Magnetoresistance and efficiency measurements of indium tin oxide/N , NЈ-diphenyl-N , NЈ bis͑3-methylphenyl͒-͑1,1Ј-biphenyl͒-4,4Ј diamine/aluminum tris͑8-hydroxyquinoline͒/cathode organic lightemitting diode structures have been made as a function of magnetic field and cathode type. It has been found that magnetoresistance occurs only when there is light emission from the devices, which suggests that the magnetoresistance is related to exciton formation. Comparison of the effects of applied field on device eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
228
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(244 citation statements)
references
References 14 publications
9
228
0
5
Order By: Relevance
“…[3][4][5] However, none of them unambiguously explain all the experimental results. Although the models for OMAR are based on different processes, ranging from bipolaron formation 5 to recombination of electron-hole (e-h) pairs 3 and detrapping of charges by triplet excitons, 4 there is also a strong similarity between these mechanisms. In the proposed models an applied magnetic field alters the spin-dependent reactions between two particles, thereby changing the current through the organic devices.…”
Section: Introductionmentioning
confidence: 62%
“…[3][4][5] However, none of them unambiguously explain all the experimental results. Although the models for OMAR are based on different processes, ranging from bipolaron formation 5 to recombination of electron-hole (e-h) pairs 3 and detrapping of charges by triplet excitons, 4 there is also a strong similarity between these mechanisms. In the proposed models an applied magnetic field alters the spin-dependent reactions between two particles, thereby changing the current through the organic devices.…”
Section: Introductionmentioning
confidence: 62%
“…Nowadays, the study of organic magneto-resistance (OMAR) is of great importance in the framework of organic spintronics and it introduces a new scenario of possible applications [6,7]. Spin dependent charge recombination, spin blocking bipolaron formation and triplet-polaron scattering were proposed as possible explanations [8][9][10]. Furthermore, experimental evidence showed that trapping centers may be related to OMAR, suggesting that more mechanisms may participate to the magnetoresistance [11].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] The effect of a magnetic field on these reactions was already considered by Ern and Merrifield in molecular crystals. 15 Desai et al 3 were the first to qualitatively describe how this can give rise to large room-temperature MC in disordered organic semiconductors. The authors consider the triplet excitons to momentarily capture polarons in states they recently referred to as charged excitons, 21 thereby reducing the polaron transport.…”
Section: Introductionmentioning
confidence: 99%
“…One competing model proposes reactions between polaronic electron and hole pairs, 2 whereas another relies on the reaction between triplet excitons and (trapped) polarons. 3,4 Conversely, the reactions of equal charges are described by a third (bipolaron) model. 5 These models have been used to explain low-field effects (LFEs), which are visible on a relatively small field scale of a few mT, as well as high-field effects (HFEs) on much broader field scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation